2022
DOI: 10.3390/curroncol29110632
|View full text |Cite
|
Sign up to set email alerts
|

Sintilimab-Induced Diabetic Ketoacidosis in a Patient with Radiation and Multichemorefractory Penile Cancer: A Case Report and Literature Review

Abstract: Penile squamous cell carcinoma (PSCC) is a rare disease. The treatment options for advanced penile cancer are often limited, and the prognosis remains poor. We reported a 52-year-old male recurrent and metastatic PSCC patient with high PD-L1 expression (90%) and TMB (14.4 muts/Mb). He had undergone penectomy, bilateral inguinal lymph node dissection, and excision of the abdominal wall mass. Despite cisplatin-based concurrent chemoradiotherapy and sequential chemotherapy with docetaxel plus cisplatin then being… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Sintilimab is a recombinant humanized lgG4 anti-PD-1 antibody, with affinity to human programmed cell death protein 1 (PD-1). Lv et al ( 57 ) reported that a patient of recurrent and metastatic penile squamous cell carcinoma obtained progression-free survival with continuous sintilimab. Immune-based treatments coupled with systemic therapy may offer benefits to patients with advanced penile cancer ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sintilimab is a recombinant humanized lgG4 anti-PD-1 antibody, with affinity to human programmed cell death protein 1 (PD-1). Lv et al ( 57 ) reported that a patient of recurrent and metastatic penile squamous cell carcinoma obtained progression-free survival with continuous sintilimab. Immune-based treatments coupled with systemic therapy may offer benefits to patients with advanced penile cancer ( 58 ).…”
Section: Discussionmentioning
confidence: 99%